Pengaruh Promosi, Variasi Produk dan Harga terhadap Minat Beli pada UD Saudara di Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Consumer purchasing interest is a crucial aspect in determining the expansion of a company. A company has good expansion if it can attract consumers in deciding to purchase products from a market that gets a positive response from consumers. Promotion, product variety and price are factors that are thought to stimulate positive emotional responses from consumers as an effort to increase consumer buyying interests. The aim of this researcsh is to determines the influences ofs promotions, product variations and prices ons purchasing interest at UD Saudara in Denpasar. This researcsh was conducted at UD Saudara in Denpasar with a sampel size of 96 people using a random sampling methods. Primary data collection was carried out using a questionnaire. The analytical method used is multiple linear regression analyssis using the SPSS version 26 program. The results of the analyssis show that 1) promotion has a positive and signifficant effect on buying interest, 2) product variety has a positive and signifficant effect on buying interest, 3) price has a positive and signifficant effect on buying interest, 4) promotion, product variety and price have a positive and signifficant effect on buying interest.